Penerapan Pembelajaran Tipe Co-op Co-op dan Team Games Tournament (TGT) pada siswa SMP dengan Materi Pelaku Ekonomi dan Perannya dalam Kegiatan Ekonomi - Saniyasa, Made; Tripalupi, Lulup Endah (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This research uses collective learning approaches and Team Games Tournaments to look at students' learning achievements. The study is now underway in SMP Negeri 8 Singaraja's grade VIII, including two classrooms. Tests are used to acquire data. Statistics and hypothesis tests are used to analyze the results. This study revealed that the experimental and control groups had substantial disparities in student learning outcomes. The experimental group that used TGT got significantly better results than the control group that used collaborative form learning. Students who used cooperative learning strategies received an average score of 72.38, while those who used the TGT learning model received an average score of 83.6.